1987
DOI: 10.1007/bf00314190
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic disturbances and cardiovascular reflexes in idiopathic Parkinson's disease

Abstract: A total of 22 patients suffering from idiopathic Parkinson's disease and 20 age-matched volunteers were questioned about autonomic disturbances and all underwent four non-invasive tests examining cardiovascular reflexes. Significantly more autonomic disturbances were reported by the patients than by the controls. Resting blood pressure was significantly decreased in patients taking dopamine agonists, whereas it was normal in those patients who only received levodopa and anticholinergics. Resting heart rate and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0
3

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 25 publications
5
47
0
3
Order By: Relevance
“…To the best of our knowledge, prior studies have focused on group comparisons ,ofter reaching contradictory results [1,3,16,20,21,25,28,29,32,33,35]. It should be noted that, even if a significant statistical difference associated to a certain feature is consistently revealed across several studies, this is not sufficient to demonstrate its potential application to the clinical necessity of single-subject characterization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, prior studies have focused on group comparisons ,ofter reaching contradictory results [1,3,16,20,21,25,28,29,32,33,35]. It should be noted that, even if a significant statistical difference associated to a certain feature is consistently revealed across several studies, this is not sufficient to demonstrate its potential application to the clinical necessity of single-subject characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Within these reports, conflicting evidence exists about the extent and characteristics of PD-related aberrations in cardiovascular control. As an example, two studies have described orthostatic hypotension and a decreased heart rate response to the Valsalva maneuver [1,28], while other authors have found that pressure and heart rate response during these procedures remained normal [25,33].…”
Section: Introductionmentioning
confidence: 99%
“…Ludin SM, and Steiger UH et al analysed cardiovascular reflexes in 22 patients and have concluded the heart rate variation evoked by deep breathing as well as the blood pressure response and the heart rate response to sustained isometric exercise were significantly diminished in the patients with idiopathic Parkinson's disease. 24 Piha SJ, Rinne JO, Rinne UK et al in their study of Autonomic dysfunction in recent onset and advanced Parkinson's diseas Maetzler W et al and Goldstein DS et al, have concluded that in Parkinson's disease a parasympathetic damage occurs which worsens during the course of the disease, and also the orthostatic fall in blood pressure, indicating a sympathetic dysfunction. [25][26][27][28] The dysfunction of cardiovascular autonomic control is thought to correlate with the severity of the disease (Van Dijk et al).…”
Section: Autonomic Function Testsmentioning
confidence: 98%
“…The autonomic cardiovascular function in PD was demonstrated previously using various tests. The results of autonomic cardiovascular function tests such as the Schellong test, the head-up tilt test, and the Valsalva maneuver have been reported to be variably impaired in PD patients [21,22,23]. The plasma norepinephrine concentration is used as an index of sympathetic denervation.…”
Section: Discussionmentioning
confidence: 99%